Impact of Management Education on Skill Development: A Study of Alumni of Management Institutes in Kerala State - Nair, Dr. V. Raman; Mathew, Mr. George K. (Ushus Journal of Business Management, 2021)
Management education in India gained demand with the opening of the economy in 1991. Many institutes and colleges have come up since then to offer Post Graduate courses like Master of Business Administration (MBA) and Post Graduate Diploma in Management (PGDM) to the students. There is a widely prevalent perception among all stake holders that the quality of management education has been suffering, with only about 10% of the B-School graduates employable, which in turn has been attributed to the lack of employability skills among the B- school graduates. The study identified the key dimensions of employability skills perceived to be beneficial through a survey of alumni from the Kerala based management institutes. The set of higher education skills expected of management graduates, as per the Framework for Higher Education Qualification (FHEQ) in UK was combined with employability skills propounded by other researchers and assessed with 28 qualification descriptors under six dimensions for employability skills.